Taxonomic revision of West African cone snails (Gastropoda: Conidae) based upon mitogenomic studies: implications for conservation - Tenorio, Manuel J.; Abalde, Samuel; Pardos-Blas, José R.; Zardoya, Rafael (European Journal of Taxonomy, 2020)
In the last few years, a sharp increase in the number of descriptions of new species of West African cone snails, particularly from the Cabo Verde Archipelago, has taken place. In previous studies, we used mitogenome sequences for reconstructing robust phylogenies, which comprised in total 120 individuals representing the majority of species (69.7%) described from this biogeographical region (except Angolan endemics) and grouped into seven genera within the family Conidae. Here, we add another 12 individuals representing endemic species that were missing in the previous studies. We use the phylogenies to identify monophyletic groups and a genetic divergence threshold (0.2% uncorrected p distance) to determine the number of valid species. As a result, the number of valid West African cone species could be drastically reduced to at least 40%, indicating that some recent poor-quality descriptions loosely based on phenotypic characters prone to convergence such as the shape and color patterns of the shell have contributed substantially to taxonomic inflation. Several previously accepted species with a reduced geographical distribution now become phenotypic forms of the remaining valid species, which increase their distribution ranges. In contrast, several cryptic species are now uncovered and described. For instance, Africonus insulae sp. nov. and Kalloconus canariensis sp. nov. are hereby introduced as new species. A detailed systematic account with illustrations and relevant information is presented. Lectotypes are designated for Conus trochulus and Conus irregularis, and neotypes for Conus crotchii and Conus diminutus. According to our results, it is strongly recommended that any future introduction of new taxa names for cone snails from West Africa should be supported by molecular and/or anatomical rather than exclusively shell morphological data. The taxonomic decisions here taken have direct implications for conservation and will eventually require re-evaluation of the Red List risk status of an important number of species.